Dampak Motivasi Kerja, Kepuasan dan Kinerja Polisi Wanita - Diana Pramudya Wardhani; Sri Hartono (Jurnal Manajemen Dayasaing, 2020)
The organization's ability to successfully achieve its goals is supported by internal and external factors of the organization. Employee performance is generally driven by security, social, self-actualization rewards. The female police force has grown rapidly. However, almost no research has examined the motivation of policewomen to join law enforcement and performance. The purpose of this study was to determine and analyze the impact of work motivation on female police by mediating job satisfaction of the police, totaling 61 people at the Ponorogo Police. Data collection in this study was carried out through a survey approach through quantitative descriptive research by distributing questionnaires to 61 respondents. The data analysis method used is path analysis. The results showed that work motivation has an influence on job satisfaction. The second result, work motivation has an influence on performance and the third result of job satisfaction has an influence on performance. The overall findings for this study suggest that motivation theory is an explanatory framework where organizational identification impacts job satisfaction. Moreover, it is inversely related to satisfaction not shown to play a mediating role in the relationship between motivation and performance of female police officers